Interpersonal Apologies: a Psychological Perspective of How They Might Work in Law - Allan, Alfred (Oñati Socio-Legal Series, 2017)
Apologies have become an accepted feature in many fields of law and there is evidence that they make a constructive contribution to the resolution of disputes. The reason for this might be that they address the intangible needs of parties after adverse events that law otherwise find difficult to address. Legal reformers introduced apologies into law primarily on the basis of deductive reasoning without being able to refer to a comprehensive psychological theory that explains the apology process; in part because apology was only identified as a psychological construct worthy of empirical research during the last quarter of the 20th century. Researchers’ contributions since the 1980s greatly improved the knowledge base about the apology process and we reviewed the relevant literature to find a comprehensive integrated theory of apology that legal reformers and practitioners can use to understand and predict the apology process. We could not find such a theory, but we try to integrate the empirical findings regarding interpersonal apologies into a rudimentary explanation that we believe could assist them. We conclude that apologies will generally be a part of the negotiated corrective interaction between the parties and that legislation should accommodate the process without being overly prescriptive and that lawyers should therefore refrain from judging the apologies their clients offer or accept.